Deciphering the active constituents of Dabushen decoction of ameliorating osteoarthritis via PPARγ preservation by targeting DNMT1 - Lu Qiu; Lu Qiu; Min Zhang; Min Zhang; Chenghao Li; Chenghao Li; Yehu Hou; Yehu Hou; Hao Liu; Hao Liu; Jia Lin; Jia Lin; et al. (Frontiers Media S.A., 2022)
Osteoarthritis (OA) is a multifactorial and chronic degenerative joint disease. Due to the adverse effects of currently used drugs, a safer and more effective therapy for treating OA is needed. Peroxisome proliferator-activated receptor-γ (PPARγ) is a key protein protecting cartilage. DNMT1-mediated hypermethylation of PPARγ promoter leads to its suppression. Therefore, DNMT1 might be an effective target for exerting cartilage protective effects by regulating the epigenetic expression of PPARγ. Dabushen decoction (DD) is a representative prescription of Dunhuang ancient medical prescription, which has a potential therapeutic effect on OA. So far, the research of the efficacy and material basis of DD in the treatment of OA remains unclear. In this study, Micro-CT, HE staining, S-O staining, and immunohistochemistry analysis were used to demonstrate that DD increased the expression of PPARγ and collagen synthesis in an OA rat model. Next, the structure of DNMT1 was used to screen the active constituents of DD by molecular docking method for treatment OA. Seven potential active constituents, including isoliquiritigenin, emodin, taxifolin, catalpol, alisol A, zingerone, and schisandrin C were hited. The protective effect of the potential active constituents to chondrocytes were evaluated by protein capillary electrophoresis, immunofluorescence assays, and ex vivo culture of rat knee cartilage. The five constituents, such as alisol A, emodin, taxifolin, isoliquiritigenin, and schisandrin C could promote the expression of PPARγ and ameliorate IL-1β-induced downregulation of collagen II and the production of MMP-13. Alisol A and Emodin could effectively mitigate cartilage damage. At last, molecular dynamics simulations with MM-GBSA method was applied to investigate the interaction pattern of the active constituents and DNMT1 complexes. The five constituents, such as alisol A, emodin, taxifolin, isoliquiritigenin, and schisandrin C achieved a stable binding pattern with DNMT1, in which alisol A has a relatively high binding free energy. In conclusion, this study elucidates that the active constituents of DD (alisol A, emodin, taxifolin, isoliquiritigenin, and schisandrin C) could ameliorate osteoarthritis via PPARγ preservation by targeting DNMT1.These findings facilitated clinical use of DD and provided a valuable strategy for developing natural epigenetic modulators from Chinese herbal formula.